BIOLOGICAL INVESTIGATION OF A NATURAL POLYSACCHARIDE BLEND: FROM ANTHELMINTIC ACTIVITY IN EARTHWORMS TO CYTOTOXICITY IN BREAST CANCER CELLS - Sharma, Ritika; Shreyas; Umadevi. A; Aleesha, Shaik; D.Chinababu; Ashima Devi; Mukherjee, Rajesh Kumar; Ranpara, Rajan N (Cuestiones de Fisioterapia, 2025)
The present study evaluates the anthelmintic and cytotoxic activities of a polysaccharide blend (OPASP), composed of Okra polysaccharide (OP) and Angelica sinensis polysaccharide (ASP) in a 1:1ratio, against Pheretima posthuma earthworms and human cancer cell lines (MCF7, HepG2, and A549).The anthelmintic activity of OP-ASP was assessed using an in vitro assay, comparing its effects withAlbendazole, a standard anthelmintic drug. The results demonstrated a dose-dependent response, withOP-ASP showing significant paralysis and death times comparable to Albendazole at higherconcentrations. The MTT test was utilised to assess the cytotoxicity of OP-ASP in MCF7 (breastcancer), HepG2 (liver cancer), and A549 (lung cancer) cells.